A Speech Based Algorithm for Watermarking Relational Databases - Haiqing Wang; Xinchun Cui; Zaihui Cao (International Symposium on Information Processing, ISIP 2008 : International Pacific Workshop on Web Mining and Web-Based Application, WMWA 2008, Moscow, Russia, 23-25 May 2008, 2008)
This paper studies a novel scheme of watermarking relational databases for copyright protection. Speech signal is introduced as watermark to be embedded into the relations; associated novel watermark insertion algorithm and detection algorithm are proposed. Thus, the watermark signal in this method is expected to be more meaningful and has closer correlative to the copyright holder. Experimental results verify that the proposed method is feasible, effective and robust.